Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Prestasi Belajar Siswa di SMK Negeri 1 Mojosongo - Wahyu Rizki Akbar; Triono Ali Mustofa (Journal on Education, 2023)
The background of this research is to look at developments at SMK N 1 Mojosongo which are progressing rapidly in terms of quality and quantity. Where this research is formulated from, how is the principal's leadership strategy, what strategy is used in improving learning achievement, and whether the strategy applied has had an effect on student achievement at SMK N 1 Mojosongo. With the aim of knowing the principal's leadership strategy, knowing the strategy used to improve learning achievement, and to find out the results of the influence of the strategy implemented at SMK N 1 Mojosongo. Researchers conducted research using qualitative research methods, which is something that cannot be measured or described. Thus, researchers collected data by conducting interviews with school principals, observing the school environment and taking notes or documentation. The results of the study show that the principal's leadership strategy at SMK N 1 Mojosongo is successful and has an effect on increasing student learning achievement both from an academic (theory) and non-academic (practice) perspective. This is driven by the existence of a school principal's strategy, learning methods, and well-conducted evaluations